Development of Time-Resolved Fluorescence Immunochromatographic Assays for Simultaneously Detecting Tylosin and Tilmicosin in Milk in Group-Screening Manner - Yu Wang; Jin-Yi Yang; Ying He; Lu Li; Jian-Xin Huang; Yuan-Xin Tian; Hong Wang; Zhen-Lin Xu; Yu-Dong Shen (Foods, 2021)
Tylosin and tilmicosin (T&T) residues in livestock products have received extensive attention from consumers. Time-resolved fluorescence immunochromatographic assay (TRFICA), as a fast, efficient and sensitive immunoassay method, has played an increasingly important role in the food safety field. Therefore, herein a quantitative and visual TRFICA was established for simultaneously detecting T&T in milk in a group-screening manner. Under the optimal conditions, the standard curve range of developed TRFICA based on the T&T was 1.87~7.47 ng/mL, and the half-maximal inhibition concentrations (IC50) were 4.06 ng/mL and 3.74 ng/mL, respectively. The limits of detection (LOD) of the TRFICA method were from 1.72 ng/mL to 1.39 ng/mL, and the visual cut-off values were 31.25 ng/mL and 62.50 ng/mL for T&T in milk, respectively. Moreover, the stability experiments showed that the strips could be stored at 4 °C for more than 6 months, the total detection time was less than 13 min, and the cross-reactivities (CRs) with related compounds were less than 0.1%, which concluded that the developed TRFICA method could be used in real milk sample detection.